1974
DOI: 10.1073/pnas.71.7.2715
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine Oxidase and Cerebral Uptake of Dopaminergic Drugs

Abstract: The brain uptake of amines that do not enter the brain or enter it poorly was promoted by noncompetitive inhibitors of monoamine oxidase, as shown by behavioral and chemical criteria. Mice pretreated with water or enzyme inhibitors other than those mentioned were placid after receiving dopamine (3,4-dihydroxyphenethylamine). Mice pretreated with monoamine oxidase inhibitors (nialamide or iproniazid) showed upon treatment with dopamine the brisk motor responses characteristic of treatment with its precursor, L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
(22 reference statements)
1
12
0
Order By: Relevance
“…The inhibition of monoamine oxidase (MAO) activity by MB has been known for many decades (Philpot, 1937; Philpot and Cantoni, 1941; Imaizumi et al, 1959; Ehringer et al, 1961; Cotzias et al, 1974). It was reported that MB (0.5 μM) potently inhibited the activity of MAO in guinea pig liver homogenates and potentiated the vasoconstriction induced by tyramine (Imaizumi et al, 1959).…”
Section: Methylene Blue and Neurotransmitter Systemsmentioning
confidence: 99%
“…The inhibition of monoamine oxidase (MAO) activity by MB has been known for many decades (Philpot, 1937; Philpot and Cantoni, 1941; Imaizumi et al, 1959; Ehringer et al, 1961; Cotzias et al, 1974). It was reported that MB (0.5 μM) potently inhibited the activity of MAO in guinea pig liver homogenates and potentiated the vasoconstriction induced by tyramine (Imaizumi et al, 1959).…”
Section: Methylene Blue and Neurotransmitter Systemsmentioning
confidence: 99%
“…The means and standard errors of the effects of apomorphine (Table 3), scored by a system different from that used for levodopa (30), were diminished by cycloheximide, chloramphenicol, and puromycin in intact mice. Caudectomized mice treated with the apomorphine (2 jsg/g, i.p.)…”
Section: Observationsmentioning
confidence: 99%
“…The method of measuring adenylate cyclase activity has been described earlier (20). Various concentrations of morphine ranging from 1 ,uM to 5 mM in either 50 ,ul of solution or in 25 Al together with 25 ,l of 5 mM dopamine or 25 ,uM naloxone were added to the homogenates prior to the addition of ATP, which initiates the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Caudate nuclei of the mice were excised as for the adenylate cyclase determination and homogenized in 6 ml of 50 mM Tris-HCl, pH 7.5. Aliquots (1.9 ml) each of the homogenates were incubated for 5 min at 35°in triplicate with one of the following: 25 ,l of 0.1 ,uM morphine, 25 ,ul of 5 mM dopamine, 25 ,l of 0.1 ,uM morphine plus 5 ml of cold Tris-HCI. One milliliter of 10% sodium dodecyl sulfate was added to the dried filters, which were shaken in scintillation vials for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation